ALGORITHM FOR TACTICS OF SURGICAL TREATMENT IN PATIENTS WITH PROXIMAL TIBIA FRACTURES - Chip, Ye.E.; Kalashnikov, A.V.; Kalashnikov, O.V. (World of Medicine and Biology, 2020)
The purpose of the study performed was: to develop an algorithm for tactics for surgical treatment of patients with fractures of the proximal tibia. The algorithm was based on the analysis of domestic and foreign literature sources, the results of own clinical studies on the treatment efficacy in 125 patients with proximal tibia fractures, who were treated at the clinic of the SI “ITO NAMS of Ukraine” and the Traumatology Department of KNMP “Globyne Central District Hospital” in 2008-2017, and biomechanical studies to determine the strength of fixation using different methods of osteosynthesis in proximal tibia fractures. Based on our own clinical and biomechanical studies, analysis of literature sources, an algorithm for surgical treatment tactics in patients with proximal tibia fractures has been developed, which will permit effective treatment of this severe orthopedic pathology at all stages of surgery. The developed algorithm permits a differentiated selection of surgical accesses, repositions and methods of bone fragments fixation, improves the efficacy of surgical treatment in patients with proximal tibia fractures and can be recommended for implementation in our country.